Ordinance No. 9: Carrying Deadly Weapons, Jan. 28, 1873, reprinted in Arizona Weekly Citizen, Feb. 8, 1873, at 2 - (:unkn) unknown (My University, 1873)
Prohibited the wear or carry of any dirk, dirk-knife, gun, pistol, sword-cane, slung-shot, or other dangerous or deadly weapon. Violators fined not exceeding ten dollars, or imprisoned not exceeding ten days, or both.
Keywords: CARRY